"I am the androgyne": Reflections on Gender and Language in the Poetry of Sylvia Plath, Anne Sexton and Adrienne Rich - Pérez Novales, Marta (Miscelánea: A Journal of English and American Studies, 1992)
In this essay, some lines from Adrienne Rich's “The Stranger” serve as the starting point for an outline of the standard approaches to women's language in contemporaryAnglo-American and French feminism. The work of three representative American female poets —Sylvia Plath, Anne Sexton and Adrienne Rich— is considered, in order to illustrate the theoretical issues discussed in the first part of the essay. A conclusion follows, in which androgyny is propounded as a useful concept in characterising contemporary women’s poetry.